KONSTRUKSI TINDAKAN KORUPSI PADA FILM “NEGERI TANPA TELINGA” - Prema Utami, Ni Putu Shanti; Sugiarica Joni, I Dewa Ayu; Pradipta, Ade Devia (E-Jurnal Medium, 2018)
ABSTRACT                                                     Film becomes an aesthetics work of art as well as an information tool that sometimes can be a means of entertainment, tool of propaganda and even political tool. Film may create different perception according to the message in it. Corruption is one of topics which often discussed in many media, such as print media, electronic media, even film. Theeobjectiveeoffthissstudyiisstoeexplainttheemeaningoofccorruption in film entitled Negeri Tanpa Telinga. Data were collected from video, images, and dialogues in the film and were analyzed by Charles Sanders Pierce’s semiotics textual analysis. This studyyfounddthattthe characteristics of corruption inttheefilm inntheeform of bribery, embezzlement, smuggling, giving (gifts or grants), manipulation of the authority, related to occupation of someone or the profession, neatly and structured. Then, the influence and role of women becomes very important in the continuity of corruption such as reward for corrupt and become the good member on the group in preparing a strategy of corruption than men. Furthermore, this film depicted a new image about women’s role in corruption, especially in Indonesia. The result of this study constructed as well by the director on relation about politics in Indonesia.   Keyword: Analysis, Semiotics, Film, Corruption